A Retrospective Study on Anthropometrical, Physical Fitness, and Motor Coordination Characteristics That Influence Dropout, Contract Status, and First-Team Playing Time in High-Level Soccer Players Aged Eight to Eighteen Years. Issue 6 (June 2015) - Deprez, Dieter N.; Fransen, Job; Lenoir, Matthieu; Philippaerts, Renaat M.; Vaeyens, Roel
Abstract : Abstract: Deprez, DN, Fransen, J, Lenoir, M, Philippaerts, RM, and Vaeyens, R. A retrospective study on anthropometrical, physical fitness, and motor coordination characteristics that influence dropout, contract status, and first-team playing time in high-level soccer players aged eight to eighteen years. J Strength Cond Res 29(6): 1692–1704, 2015—The goal of this article was twofold, and a 2-study approach was conducted. The first study aimed to expose the anthropometrical, physical performance, and motor coordination characteristics that influence dropout from a high-level soccer training program in players aged 8–16 years. The mixed-longitudinal sample included 388 Belgian youth soccer players who were assigned to either a "club group" or a "dropout group." In the second study, cross-sectional data of anthropometry, physical performance, and motor coordination were retrospectively explored to investigate which characteristics influence future contract status (contract vs. no contract group) and first-team playing time for 72 high-level youth soccer players (mean age = 16.2 years). Generally, club players outperformed their dropout peers for motor coordination, soccer-specific aerobic endurance, and speed. Anthropometry and estimated maturity status did not discriminate between club and dropout players. Contract players jumped further ( p = 0.011) and had faster times for a 5-m sprint ( p = 0.041) than no contract players. The following prediction equation explains 16.7% of the variance in future playing minutes in adolescent youth male soccer players: −2, 869.3 + 14.6 × standing broad jump. Practitioners should include the evaluation of motor coordination, aerobic endurance, and speed performances to distinguish high-level soccer players further succeeding a talent development program and future dropout players, between 8 and 16 years. From the age of 16 years, measures of explosivity are supportive when selecting players into a future professional soccer career.